Analysis of Students’ Interest and Motivation to Learn Physics at a School for Sports Excellence - Aini, Mirza; Mufit, Fatni; Akmam, Akmam; Sundari, Putri Dwi (Universitas Negeri Padang, 2023)
Students' interest and motivation to learn physics at the School of Sports Excellence has an important role in influencing students' academic achievement. However, in reality the interest and motivation of students at the School of Sports Excellence to learn physics found in the field is still low. This study aims to analyze the interest and motivation to learn physics of students at the School of Sports Excellence. This research uses survey method with data collection technique using questionnaire. The data analysis technique used percentage technique. This research was limited to class XI MIPA totaling 29 students as a sample. The results showed that students' interest and motivation to learn physics were low. The results of questionnaire analysis of student interest and motivation to learn physics are categorized as low, a strategy is needed to increase student interest and motivation to learn physics. The implication of this research is that educators should consider differences in students' interest and motivation to learn in designing appropriate curriculum and supportive teaching methods. With a better understanding of the factors that influence interest and motivation to learn physics, education in sport speciality schools can be more effective.